Involvement of corporate entities in Waqaf management: experiences of Malaysia and Singapore - Md Saad, Norma; Kassim, Salina; Hamid, Zarinah (Asian Economic and Social Society, 2013)
The main focus of this paper is to examine the corporate management models of selected waqaf entities in Malaysia and Singapore. The waqaf entities involved in this study include two corporate waqaf institutions namely Kumpulan Waqaf An-Nur Berhad and IIUM Endowment Fund and one corporate waqaf institution in Singapore namely Warees Private Limited, Majlis Ugama Islam Singapore. It also analyzes how these waqaf entities finance the development of their waqaf property, especially land. Such a comparison is necessary considering the diverse experiences of these selected corporate waqaf entities in view of the differences in their endowments and different corporate management models. The paper concludes that these three corporate waqaf entities have adopted a more structured approach in financing the development of their waqaf properties and experimenting new ways of managing and investing waqaf assets. They have created opportunities for the improvement of waqaf institutions and revitalize the potentials of these waqaf assets to yield greater benefits to the society.